RANCANG BANGUN APLIKASI PEMBELAJARAN IQRA’ INTERAKTIF BERBASIS MOBILE - Azella Septary; Ahmaddul Hadi (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
The purpose of this study was to design and build an IQRA learning application consisting of reading and listening to how the correct hijaiyah reading, harokat, tanwin, tajwid and sound pronunciation testing. The development of this application uses tools and tools for developing the Android programming language and uses voice recognition, the algorithm implemented is a video and conquer algorithm. The initial process is to convert sound spectrum data into digital form and change it in discrete form. It is from the discrete form that then applies the divide algorithm and conquer to optimize the timing of speech recognation matching. A test has been carried out which results from testing this application that there is agreement between the algorithm and the design of the application that has been made and tested by experts or religious teachers who understand and explore the science in their fields.Keywords: hijaiyah, android, interactive, voice recognation